The correlation between visual fatigue and duration of viewing as assessed by brain monitoring. Issue 7 (5th June 2018) - Yue, Kang; Wang, Danli; Hu, Haichen; Fang, Sun
Abstract: Duration of viewing was considered as one of the most important factors of 3D visual fatigue. However, their relationship was not well studied. We proposed to use brain monitoring techniques to reveal more details about the variety of brain activity while watching three‐dimensional (3D) content. We investigated the spectral patterns in the electroencephalogram related to various duration of viewing and showed the power spectral density varied significantly along with the development of fatigue over occipital lobe, parietal lobe, and right frontal lobe. Moreover, we first described the trend of brain activity during 3D content viewing and revealed the location of significant components related to 3D visual fatigue. We believe that the absolute power describes more information and may be a better indicator of 3D visual fatigue assessment compared with relative power. We also first revealed the cortex location that is related to 3D visual fatigue. Our findings may help to define appropriate electroencephalogram features for online 3D visual fatigue detection while participants viewing 3D content. Abstract : We proposed to use brain monitoring techniques to reveal more details about the variety of brain activity while watching three‐dimensional content. We investigated the spectral patterns in the electroencephalogram related to various duration of viewing and showed the power spectral density varied significantly along with the development of fatigue over occipital lobe, parietal lobe, and right frontal lobe. We first described the trend of brain activity and revealed the location of significant components related to three‐dimensional visual fatigue.